Biomarkers Obtained by Transcranial Magnetic Stimulation in Neurodevelopmental Disorders. Issue 2 (February 2022) - Jannati, Ali; Ryan, Mary A.; Kaye, Harper L.; Tsuboyama, Melissa; Rotenberg, Alexander
Abstract : Summary: Transcranial magnetic stimulation (TMS) is a method for focal brain stimulation that is based on the principle of electromagnetic induction where small intracranial electric currents are generated by a powerful fluctuating magnetic field. Over the past three decades, TMS has shown promise in the diagnosis, monitoring, and treatment of neurological and psychiatric disorders in adults. However, the use of TMS in children has been more limited. We provide a brief introduction to the TMS technique; common TMS protocols including single-pulse TMS, paired-pulse TMS, paired associative stimulation, and repetitive TMS; and relevant TMS-derived neurophysiological measurements including resting and active motor threshold, cortical silent period, paired-pulse TMS measures of intracortical inhibition and facilitation, and plasticity metrics after repetitive TMS. We then discuss the biomarker applications of TMS in a few representative neurodevelopmental disorders including autism spectrum disorder, fragile X syndrome, attention-deficit hyperactivity disorder, Tourette syndrome, and developmental stuttering.